2021
DOI: 10.1007/s11191-021-00259-2
|View full text |Cite
|
Sign up to set email alerts
|

South African Grade 12 Science Students’ Understandings of Scientific Inquiry

Abstract: The ability to do inquiry does not necessarily translate to understandings about scientific inquiry or the processes by which scientific knowledge is generated. The study reported in this paper focuses on what students know about scientific inquiry and what impact school science may have on this knowledge. We investigated grade 12 physical and life sciences students' understandings about eight core aspects of the nature of scientific inquiry (NOSI) at a diversity of high schools in South Africa. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…Previous research in the field, on the other hand, concentrated on the relationship between science achievement and understanding of SI. Penn et al (2019), for instance, examined the relationship between 12th grade students' understanding of SI and achievement scores obtained from a high-stake exam in South Africa. Similar to this research, their results showed that understandings about nature of SI was positively correlated with their achievement scores in physical sciences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research in the field, on the other hand, concentrated on the relationship between science achievement and understanding of SI. Penn et al (2019), for instance, examined the relationship between 12th grade students' understanding of SI and achievement scores obtained from a high-stake exam in South Africa. Similar to this research, their results showed that understandings about nature of SI was positively correlated with their achievement scores in physical sciences.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that students who have a strong understanding of SI have better metacognitive skills that allow them to apply their knowledge across different subjects. To this end, Penn et al (2019) argues that learners who engage in scientific inquiry describe objects and events, pose questions, create explanations, test those explanations against existing scientific knowledge, and share their ideas with others. The authors suggest that through these activities, learners use and develop higher-order reasoning and thinking skills which ultimately help them build their understanding by integrating knowledge with their own ideas and experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pembelajaran IPA saat ini secara global didominasi oleh pendekatan sains sebagai inkuiri (Aditomo & Klieme, 2020;Bansal, 2021;Herranen & Aksela, 2019;Mutlu, 2020;Penn & Ramnarain, 2022). Proses penyelidikan yang ditranslasikan dalam sebuah metode ilmiah dalam sains, juga dijadikan sebagai "jiwa" dalam proses pembelajaran IPA di sekolah.…”
Section: Pendahuluanunclassified
“…Pendekatan inkuiri induktif terbimbing tidak hanya difokuskan pada aktivitas "doing inquiry" saja, tetapi juga penguatan kombinasi instruksi atau petunjuk eksplisit dan reflektif tentang proses yang berbeda dari guru serta urutan penyajian masalah dan aktivitas belajar. Pengemasan scaffolding dan peran guru dalam proses pembelajaran berbasis inkuiri akan memastikan bahwa siswa mengetahui metode inkuiri yang digunakan, pertanyaan ilmiah yang akan diteliti dan dijawab, prosedur yang harus diikuti untuk pengumpulan data dan bukti, serta penjelasan ilmiah berdasarkan data yang dikumpulkan (Penn & Ramnarain, 2022). Agar proses pembelajaran IPA berbasis inkuiri sukses, maka pengembangan kompetensi pedagogi guru IPA dalam mengajarkan keterampilan praktik ilmiah perlu juga diperhatikan dan ditingkatkan.…”
Section: Hasil Dan Pembahasanunclassified